Language, thought, art & existence : creative nonfictions - Mwanaka, Tendai R. (Langaa Research & Publishing CIG, 2017)
This book comprises 19 creative non-fiction pieces and essays centred around the topics of language, thought, art and existence seen through the prism of practising artist in contemporary Africa. The collection continues with Zimbabwe's Tendai Mwanaka's creative non-fiction ideology of presenting non-fiction in a creative, fresh, easy reading, simple language. With most of the essays driven by personal stories, the author ably renders them accessible to a wide spectrum of readers from the scholarly to the journalistic and the general. The pieces are grouped according to the topics, with the language essays starting the book, followed by thought, existential, and art essays. In tune with the adage the personal is political, Mwanaka lets the personal drive these essays as he tries to investigate and conversationally navigate his thoughts, beliefs, feelings and experience on language, existence and art. This is an invaluable contribution to the academic establishment, social theorists, linguists, literary theorists, journalists, activists and the general readership.